2019
DOI: 10.1186/s12877-019-1289-6
|View full text |Cite
|
Sign up to set email alerts
|

Improved outcome in hip fracture patients in the aging population following co-managed care compared to conventional surgical treatment: a retrospective, dual-center cohort study

Abstract: Background: Hip fracture patients in the aging population frequently present with various comorbidities, whilst preservation of independency and activities of daily living can be challenging. Thus, an interdisciplinary orthogeriatric treatment of these patients has recognized a growing acceptance in the last years. As there is still limited data on the impact of this approach, the present study aimed to evaluate the long-term outcome in elderly hip fracture patients, by comparing the treatment of a hospital wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 34 publications
(39 reference statements)
3
34
0
9
Order By: Relevance
“…1, all studies but one [29] reported data on LOS, while data on in-hospital mortality were reported in 23 studies [16, 20, 22-25, 27, 31-33, 35-38, 43-46, 48-52]. In contrast, only about half of the studies reported data on TTS [21-25, 30, 32-35, 38, 39, 42-47, 51], complication rates [17, 20, 22, 25, 28, 32, 33, 35-39, 41, 43-45, 47, 51], and 1-year mortality [18,27,31,32,35,38,39,41,42,44,[47][48][49][50]. 30-day readmission rate [18,33,35,37,41,45], functional outcomes [18, 21-23, 27, 34], and cost [21,26,29,31,40] were reported in less than a quarter of the studies.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…1, all studies but one [29] reported data on LOS, while data on in-hospital mortality were reported in 23 studies [16, 20, 22-25, 27, 31-33, 35-38, 43-46, 48-52]. In contrast, only about half of the studies reported data on TTS [21-25, 30, 32-35, 38, 39, 42-47, 51], complication rates [17, 20, 22, 25, 28, 32, 33, 35-39, 41, 43-45, 47, 51], and 1-year mortality [18,27,31,32,35,38,39,41,42,44,[47][48][49][50]. 30-day readmission rate [18,33,35,37,41,45], functional outcomes [18, 21-23, 27, 34], and cost [21,26,29,31,40] were reported in less than a quarter of the studies.…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…Of the 37 included studies, only ten studies were RCTs [16][17][18][19][20][21][22][23][24][25]. Six studies were prospective cohort studies [26][27][28][29][30][31], ten were prospective cohort studies with a retrospective control [32][33][34][35][36][37][38][39][40][41], ten were retrospective cohort studies [42][43][44][45][46][47][48][49][50][51], and one study was a prospective pre-and post-intervention study [52]. Results of the Cochrane collaboration's tool for assessing risk of bias are given in Table 2.…”
Section: Risk Of Bias In the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be interpreted as orthogeriatric treatment especially preventing early readmissions while having a lesser impact with longer follow-up. According to one previous study, orthogeriatric treatment has been associated with decreased mortality and a lower readmission rate [33] whereas such association has not been reported in other studies [2], including a randomized controlled trial [14]. In all these studies, the orthogeriatric intervention has lasted longer than in our study (i.e., for 1.5-2 weeks), and we are not aware of earlier studies concerning the effect of very short orthogeriatric intervention, like ours, on readmission rates, mortality or clinical outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…The worldwide population is continuously aging, thereby leading to an increase in the prevalence of osteoporotic hip fractures. 1,2 A recent statistical estimation predicts that the patients receiving surgical interventions for hip fracture will double by 2050 owing to the aging of population. 3 Furthermore, hip fracture is a major public health challenge, for it causes serious morbidity, death, and socioeconomic burden.…”
Section: Introductionmentioning
confidence: 99%